HUBUNGAN ANTARA POLA ASUH OTORITER DENGAN KECEMASAN SOSIAL PADA SISWA SMA FREE METHODIST MEDAN - Mona Anelasari Hutahaean; Sabrini Mentari Rezeki; Siti Annisa Raudatullah; Bebi Astri Tarigan; Novita Sari Dewi Manurung; Angelin Peatricia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between authoritarian parenting styles and social anxiety in students of SMA Free Methodist Medan. This study uses a quantitative method with a correlational approach. The sample consisted of 139 students selected through a proportional stratified random sampling technique. The instruments used were a 35-item authoritarian parenting scale and a 32-item social anxiety scale. Both scales have undergone validity and reliability tests, with Cronbach's Alpha coefficients of 0.976 for authoritarian parenting styles and 0.977 for social anxiety, respectively. Based on the results of the research that has been carried out, it can be concluded that there is a significant influence between authoritarian parenting styles to social anxiety in students of SMA Free Methodist Medan, which is indicated by a correlation analysis, namely the Pearson Correlation value with a one-way significance level (Sig. 1-tailed) and the results of the analysis show a correlation coefficient value of 0.937 with a significance level of 0.000 (p <0.05). The regression analysis results showed an F value of 979.522 and p value of 0.000 (p < 0.05). This indicates that authoritarian parenting has a strong relationship with the level of social anxiety in SMA Free Methodist Medan students, with an effective contribution of 87.7% (Adjusted R Square = 0.876).